KAJIAN PROFIL RUJUKAN PADA KASUS PRE EKLAMSIA DI RSUD DATU SANGGUL RANTAU : Referral Profile Study On Pre-Eclampsia Cases At Datu Sanggul Rantau Hospital - Etniati, Daniela; Lathifah, Nur; Friscila, Ika (LPPM - STIKES Pemkab Jombang, 2024)
One of the complications of pregnancy/delivery is pre-eclampsia/eclampsia. Objective is knowing the description of the referral profile in the case of pre-eclampsia at Datu Sanggul Rantau Hospital. Quantitative research was conducted in February 2023. The population was all pregnant, postpartum and postpartum women with pre-eclampsia cases from January 2021 - November 2022 totaling 122 cases. The total sampling technique was analyzed using univariate. The results of the study showed that the highest number of each characteristic was the origin of referrals, namely 84 people (69%), the highest number of referrals complete with officers and referral letters, namely 89 people (73%), the age of most respondents was in the risk category > 35 years 53 people (43%), the most gestational age was term term 83 people (68%), parity was primipara 53 people (43%), the stages of delivery in the mother during intrapartum were 76 people (62%), the classification of the diagnosis of pre eclampsia in cases of pre severe eclampsia, namely 86 people (70%) and the most pre-referral action was given pre-referral action, namely 82 people (67%). The conclusion is referral profile description consists of origin, of referral completeness of referral, age, gestational age, parity, diagnosis, and pre-referral measures.